Development of a mine-used flame sensor - ZHU Chengjian; YUAN Fengpei; QIU Yu; WANG Wenlong (Gong-kuang zidonghua, 2015)
For problems of exiting flame sensors based on infrared detection principle such as short detection distance, long response time and so on, a mine-used flame sensor was developed based on ultraviolet light detection principle. Mathematical model of signal modulation circuit of ultraviolet phototube was established through experiments for calculating circuit parameters to improve response speed of the ultraviolet phototube. Power source and signal transmission circuit were designed with electro magnetic compatibility, so as to improve anti-interference ability of the sensor. The test result shows that the sensor has fast response speed, strong anti-interference ability and good stability and reliability.